Posttranscriptional Regulation of the Yersinia pestis Cyclic AMP Receptor Protein Crp and Impact on Virulence - Wyndham W. Lathem (American Society for Microbiology, 2014)
ABSTRACT The cyclic AMP receptor protein (Crp) is a transcriptional regulator that controls the expression of numerous bacterial genes, usually in response to environmental conditions and particularly by sensing the availability of carbon. In the plague pathogen Yersinia pestis, Crp regulates the expression of multiple virulence factors, including components of the type III secretion system and the plasminogen activator protease Pla. The regulation of Crp itself, however, is distinctly different from that found in the well-studied Escherichia coli system. Here, we show that at physiological temperatures, the synthesis of Crp in Y. pestis is positively regulated at the posttranscriptional level. The loss of the small RNA chaperone Hfq results in decreased Crp protein levels but not in steady-state Crp transcript levels, and this regulatory effect occurs within the 5′ untranslated region (UTR) of the Crp mRNA. The posttranscriptional activation of Crp synthesis is required for the expression of pla, and decoupling crp from Hfq through the use of an exogenously controlled promoter and 5′ UTR increases Pla protein levels as well as partially rescues the growth defect associated with the loss of Hfq. Finally, we show that both Hfq and the posttranscriptional regulation of Crp contribute to the virulence of Y. pestis during pneumonic plague. The Hfq-dependent, posttranscriptional regulation of Crp may be specific to Yersinia species, and thus our data help explain the dramatic growth and virulence defects associated with the loss of Hfq in Y. pestis. IMPORTANCE The Crp protein is a major transcriptional regulator in bacteria, and its synthesis is tightly controlled to avoid inappropriate induction of the Crp regulon. In this report, we provide the first evidence of Crp regulation in an Hfq-dependent manner at the posttranscriptional level. Our discovery that the synthesis of Crp in Yersinia pestis is Hfq dependent adds an additional layer of regulation to catabolite repression in this bacterium. Our work provides a mechanism by which the plague pathogen links not just the sensing of glucose or other carbon sources but also other signals that influence Crp abundance via the expression of small RNAs to the induction of the Crp regulon. In turn, this allows Y. pestis to fine-tune Crp levels to optimize virulence gene expression during plague infection and may allow the bacterium to adapt to its unique environmental niches.